Clay Minerals in an Active Hydrothermal Field at Iheya‐North‐Knoll, Okinawa Trough. Issue 4 (October 2015) - Miyoshi, Youko; Ishibashi, Jun‐ichiro; Shimada, Kazuhiko; Inoue, Hiroyasu; Uehara, Seiichiro; Tsukimura, Katsuhiro
Abstract Iheya‐North‐Knoll is one of the small knolls covered with thick sediments in the Okinawa Trough back‐arc basin. At the east slope of Iheya‐North‐Knoll, nine hydrothermal vents with sulfide mounds are present. The Integrated Ocean Drilling Program (IODP) Expedition 331 studied Iheya‐North‐Knoll in September 2010. The expedition provided us with the opportunity to study clay minerals in deep sediments in Iheya‐North‐Knoll. To reveal characteristics of clay minerals in the deep sediments, samples from the drilling cores at three sites close to the most active hydrothermal vent were analyzed by X‐ray diffraction, scanning electron microscope and transmission electron microscope. The sediments are classified into Layer 0 (shallow), Layer 1 (deep), Layer 2 (deeper) and Layer 3 (deepest) on the basis of the assemblage of clay minerals. Layer 0 contains no clay minerals. Layer 1 contains smectite, kaolinite and illite/smectite mixed‐layer mineral. Layer 2 contains chlorite, corrensite and chlorite/smectite mixed‐layer mineral. Layer 3 is grouped into three sub‐layers, 3A, 3B and 3C; Sub‐layer 3A contains chlorite and illite/smectite mixed‐layer mineral, sub‐layer 3B contains chlorite/smectite and illite/smectite mixed‐layer minerals, and sub‐layer 3C contains chlorite and illite. Large amounts of di‐octahedral clay minerals such as smectite, kaolinite, illite and illite/smectite mixed‐layer mineral are found in Iheya‐North‐Knoll, which is rarely observed in hydrothermal fields in mid‐ocean ridges. Tri‐octahedral clay minerals such as chlorite, corrensite and chlorite/smectite mixed‐layer mineral in Iheya‐North‐Knoll have low Fe/(Fe + Mg) ratios compared with those in mid‐ocean ridges. In conclusion, the characteristics of clay minerals in Iheya‐North‐Knoll differ from those in mid‐ocean ridges; di‐octahedral clay minerals and Fe‐poor tri‐octahedral clay minerals occur in Iheya‐North‐Knoll but not in mid‐ocean ridges.